The Effect of Competence, Motivation, and Facilities on the Productivity of PT. AKP Jetty in Marunda, North Jakarta - Sulistiyo, Sulistiyo; Fathorrahman, Fathorrahman; Pradiani, Theresia (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2025)
Productivity is an important company element which decreases make it difficult to get targets. PT. Alfa Karsa Persada (PT.AKP) is a service company supporting offshore oil companies such as warehousing and cargo handling in port. Jetty Productivity, which was expected to increase from the 2019-2023, has actually decreased. For this reason, need research variable influences such as competence, motivation and facilities. The research aim 1) does competence partially influence productivity of Jetty PT. AKP. 2) does motivation partially influence the productivity of Jetty PT. AKP. 3) do the facilities partially affect the productivity of Jetty PT. AKP. 4) do competence, motivation and facilities together influence the productivity of Jetty PT. AKP. This research approach uses descriptive quantitative sampling method used saturated sampling with 47 respondents. The analysis method uses multiple linear regression. The research showed that 70.3% of the total independent variables made an effective contribution to the dependent variable, 29.7% by other variables not examined in this research. Competence has a significant effect on productivity of Jetty PT. AKP, motivation has a significant effect on productivity of Jetty PT. AKP, and facilities do not have a significant effect on productivity of Jetty PT. AKP, can be caused by any of a material stock system from users, material under 50 kg can be handled by human power, good equipment maintenance and back up. Then competence, motivation and facilities together influence the productivity of Jetty PT. AKP. The research can be scientific evidence and a basis for companies to develop productivity.